2016
DOI: 10.5194/acp-16-2575-2016
|View full text |Cite
|
Sign up to set email alerts
|

On the effectiveness of nitrogen oxide reductions as a control over ammonium nitrate aerosol

Abstract: Abstract. Nitrogen oxides (NO x ) have fallen steadily across the US over the last 15 years. At the same time, NO x concentrations decrease on weekends relative to weekdays, largely without co-occurring changes in other gas-phase emissions, due to patterns of diesel truck activities. These trends taken together provide two independent constraints on the role of NO x in the nonlinear chemistry of atmospheric oxidation. In this context, we interpret interannual trends in wintertime ammonium nitrate (NH 4 NO 3 ) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
67
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 95 publications
(113 reference statements)
8
67
0
Order By: Relevance
“…B1-B2). Fast measurements of total NO − 3 (gas + particle, NO − 3 (g+p) ) were only available for a subset of flights (Pusede et al, 2016), and particulate-only NO − 3 measurements were not made with sufficient time resolution, less than about a minute, to allow for robust characterization of the NO − 3 (p) vertical profile. Therefore, NO − 3 (p) vertical profiles for each flight during Episode 1 are estimated from in situ measurements of dry particle scattering and the influence of water uptake on scattering, i.e., from the particle hygroscopicity, and are calibrated against the slower particle-into-liquid sampler (PILS) measurements (Appendix A, Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…B1-B2). Fast measurements of total NO − 3 (gas + particle, NO − 3 (g+p) ) were only available for a subset of flights (Pusede et al, 2016), and particulate-only NO − 3 measurements were not made with sufficient time resolution, less than about a minute, to allow for robust characterization of the NO − 3 (p) vertical profile. Therefore, NO − 3 (p) vertical profiles for each flight during Episode 1 are estimated from in situ measurements of dry particle scattering and the influence of water uptake on scattering, i.e., from the particle hygroscopicity, and are calibrated against the slower particle-into-liquid sampler (PILS) measurements (Appendix A, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This allows for a larger fraction of NO 2 to be oxidized to HNO 3 via the N 2 O 5 hydrolysis pathway (Cabañas et al, 2001;Wagner et al, 2013), and colder temperatures favor partitioning of nitrate to the particle phase (Stelson and Seinfeld, 1982). In winter, nighttime HNO 3 production can more efficiently compete with daytime photochemically driven production due to the low photolysis rates and hydroxyl radical concentrations (Wagner et al, 2013;Pusede et al, 2016). Multiday pollution events (i.e., periods with elevated particulate matter, PM, concentrations) can occur when meteorological conditions inhibit dispersion, as is the case with the persistent cold air pool formation often found in valley regions Baasandorj et al, 2017).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…On nights when NO 3 cannot accumulate in the surface layer owing to high NO emissions, N 2 O 5 uptake can still be active aloft without NO titration. The N 2 O 5 uptake aloft leads to elevated pNO − 3 formation in the upper layer as well as effective NO x removal (Watson and Chow, 2002;Pusede et al, 2016;Baasandorj et al, 2017). Field observations at high-altitude sites in Kleiner Feldberg, Germany (Crowley et al, 2010a), the London British Telecommunications tower, UK (Benton et al, 2010), and Boulder, CO, USA showed elevated N 2 O 5 concentrations aloft.…”
Section: Introductionmentioning
confidence: 99%